PEMBATALAN PERKAWINAN YANG MELEBIHI BATAS WAKTU MENURUT UNDANG – UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DAN KOMPILASI HUKUM ISLAM(STUDI PUTUSAN NOMOR 790/PDT.G/2021/PA.MKD): Juridical Analysis Of The Annulment Of A Marriage That Exceeds The Time Limit According To Law Number 1 Of 1974 Concerning Marriage And The Compilation Of Islamic Law (Study Decision Number 790/Pdt.G/2021/PA.Mkd) - Nabila Kamilia Luthfiyyah; Muriani (AMICUS CURIAE, 2025)
Marriages can be annulled for a number of reasons, including failure to meet the necessary conditions or being carried out in an unqualified manner – a marriage condition, such as being done with an invalid marriage guardian. The identification problem in this study is whether marriages of spouses who have lived together as spouses that do not meet the conditions can be annulled and whether the reason for the judge to accept the application for annulment of marriage in judgment No. 790/pdt.G/2021/PA.Mkd in accordance with the Law No. 1 of 1974 on Marriage and Compilation of Islamic Law. The descriptive aspect of the Normative Law research technique is the nature of the research in this writing and using secondary data. Based on the results and conclusion of the analysis that a legally entered marriage can be annulled, the right to seek annulment will cease after six months if the husband and wife continue to live together as spouses after learning that the preconditions for marriage are not met. The judge's decision to annul a marriage in this case would be contrary to the provisions of Article 27 para. 3 of Act No. 1 of 1974 jo. Article 72 para. (3) KHI.